Higher Education, Higher Salaries? A Case Applied to Graduates in Economics - Vasquez, Lourdes Marcela Espinoza; Cedro, Raul Rubin de Celis (Journal of Ecohumanism, 2024)
This document aims to contribute to the understanding of the determinants for choosing the Economics career in Bolivia, as well as the impact that postgraduate education has on the salary levels of graduates in this field. Regarding the latter aspect, it seeks to test whether the number of years of study following the undergraduate degree of an economist determines a higher salary level and whether postgraduate studies serve as a signal of differentiation in the labour market. To achieve the objectives outlined in this document, various linear probability econometric models are employed, constructed from the results of a survey conducted in 2024 with 79 graduates and 45 students from the Economics program at the Universidad Católica Boliviana “San Pablo.” The results suggest that the choice of the Economics career is more likely influenced by close individuals rather than by the information provided by the University about the content of the program. Furthermore, a greater number of years of study after obtaining an undergraduate degree decreases the likelihood of achieving higher salary returns, indicating signs of adverse selection within the labour market for economists in Bolivia.